PENGARUH ETANA PADA REFRIGERAN HIDROKARBON - Abidin, Zainal; Pasek, Ari Darmawan; Abdurrachim, Abdurrachim (Mesin, 2003)
Hydrocarbon refrigerant is one kind of refrigerants, which is developed to substitute CFC and HCFC. The substances contained in hydrocarbon refrigerant are etane, propane, normal butane, and iso butane. Ethane is being suspected on reducing the performance of refrigerator. This paper deals with theoretical study of ethane influence in hydrocarbon refrigerant. First of all it is necessary to create software for evaluating thermodynamics properties. This software has many choices for prescribed thermodynamics properties. According to the analysis, it is known that the more ethane content in HCR-12, the more deviation of saturated pressure-temperature curves between HCR-12 and R-12. While in HCR-22 when the pressure is less that 4 bar, it is known that the more ethane content, the more deviation of saturated pressure-temperature curve between HCR-22 and R-22. However, if the pressure is above 4 bars, it is known that the more ethane, the saturated pressure-temperature curve is close to the one of HCR-22 with 4% ethane content. On performance test of standard refrigeration system using the refrigerant, it is known that the more ethane content in HCR-12 and HCR-22, COP of the system decreases gradually. The average temperature in evaporator and condensor also declines.